Pengaruh Peraturan Pajak, Kualitas Pelayanan dan Tax Amnesty terhadap Preferensi Resiko - Septanta, Rananda; Nurhasan, Yunus; Ekarisma, Deny; Saga, Baharudin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to determine tax regulations, quality of tax services, and tax amnesty risk preferences. The population in this research is individual taxpayers registered at the Tangerang Pratama Tax Service Office. The sample in this study was one hundred individual taxpayers. The distribution of questionnaires was carried out using the convenience sampling method. Ten questionnaires were distributed, but only one hundred could be processed with a response rate of ninety percent. The data analysis technique in this research uses the classic assumption test via SPSS22. The research results show that tax amnesty and service quality influence risk preferences.